Oral Therapies for Multiple Sclerosis - Faissner, Simon (Cold Spring Harb Perspect Med, 2019)
Multiple sclerosis treatment faces tremendous changes owing to the approval of new medications, some of which are available as oral formulations. Until now, the four orally available medications, fingolimod, dimethylfumarate (BG-12), teriflunomide, and cladribine have received market authorization, whereas laquinimod is still under development. Fingolimod is a sphingosine-1-phosphate inhibitor, which is typically used as escalation therapy and leads to up to 60% reduction of the annualized relapse rate, but might also have neuroprotective properties. In addition, there are three more specific S1P agonists in late stages of development: siponimod, ponesimod, and ozanimod. Dimethylfumarate has immunomodulatory and cytoprotective functions and is used as baseline therapy. Teriflunomide, the active metabolite of the rheumatoid arthritis medication leflunomide, targets the dihydroorotate dehydrogenase, thus inhibiting the proliferation of lymphocytes by depletion of pyrimidines. Here we will review the mechanisms of action, clinical trial data, as well as data about safety and tolerability of the compounds.